2009
DOI: 10.1002/pds.1711
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyolysis reports show interaction between simvastatin and CYP3A4 inhibitors

Abstract: SUMMARY Purpose To assess spontaneous reports of rhabdomyolysis associated with simvastatin (SV) and pravastatin (PV) for evidence of CYP3A4 interaction. Clinical trial results advocate cholesterol lowering in high-risk patients including diabetics and the elderly. Given the association between advancing age, metabolic, and cardiovascular disease, many patients are treated with concomitant medications upon statin initiation. Although statins are generally safe, minor and severe adverse reactions arise, especi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 31 publications
1
35
0
1
Order By: Relevance
“…Although not studied in a clinical trial setting, case studies have reported significant interactions between fluconazole and the statins [22][23][24][25]. It is well established that increased plasma statin concentrations can be associated with rhabdomyolysis [22,26,27].…”
Section: Discussionmentioning
confidence: 97%
“…Although not studied in a clinical trial setting, case studies have reported significant interactions between fluconazole and the statins [22][23][24][25]. It is well established that increased plasma statin concentrations can be associated with rhabdomyolysis [22,26,27].…”
Section: Discussionmentioning
confidence: 97%
“…A review of the risk of rhabdomyolysis with simvastatin and pravastatin over the period 1991 to 2001 carried out by the US Food and Drug Administration (FDA) Center for Drug Evaluation and Research confirmed an association between co-administration of CYP3A4 inhibitors and simvastatin but not pravastatin [17]. The most frequent co-medications in simvastatin-associated cases were clarithromycin, mibefradil, verapamil, nefazodone, cyclosporine, diltiazem, and itraconazole.…”
Section: Drug Interactionsmentioning
confidence: 85%
“…Of the others, based upon a meta-analysis of 18 prospective randomized controlled trials (comprising 71,108 individuals), the highest rate of adverse effects, including greater than 10-fold CK elevations and rhabdomyolysis, was found to be associated with atorvastatin and the lowest risk with fluvastatin, whereas the risks for simvastatin, lovastatin, and pravastatin were intermediate and comparable [15]. Differences in pharmacodynamics and pharmacokinetics may account for these differences and it is noteworthy in this regard that atorvastatin has a much longer plasma elimination half-life (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) …”
Section: Type Of Statinmentioning
confidence: 89%
“…Essentially all statins are, in fact, substrates of membrane transporters, whereby SLCO1B1 polymorphisms can decrease the liver uptake, as well as the therapeutic potential of these agents, and may be linked to their muscular side-effects. Elevated levels of simvastatin metabolites (but not pravastatin) have been observed among carriers of SLCO1B1*5 allele, pointing to a genetic susceptibility to both myopathy and statin-induced myalgias in the absence of elevated serum creatinine kinase 167 . The risk of myalgia among SLCO1B1 carriers appears to be unique for artovastatin.…”
Section: Genetics and Drug Therapy Of Coronary Artery Diseasementioning
confidence: 99%